A Single Generalized Seizure History: An EEG Like as Status Epilepticus - Dilara MERMİ DİBEK; Arzu MAHARRAMOVA; Pınar TAMER; İbrahim ÖZTURA; Barış BAKLAN (Archives of Epilepsy, 2020)

(untitled)
Visual sensitivities include photosensitivity, eye closure sensitivity, fixation off-eye closed and pattern sensitivity. Fixation off-eye closed sensitivity occurs while eye closed and the period lasting for more than 3 s and persisting as long as the eyes remain closed or when fixation was interrupted. In this case report, a 19 years old female patient had a history of a single generalized seizure one year ago. Although there is no more seizure, electroencephalography (EEG) examination like as a status epilepticus at different times. When we examined EEG, we recognized these discharges became when eyes closed and persisted as long as eyes closed. In addition, video recording showed us eyelid myoclonus without absence during eyes closed and discharged on EEG. It is aimed to discuss the fixation-off sensitivity and eyelid myoclonus accompanied by literature with this case report.